DOI: 10.31274/rtd-180813-8685
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of alfalfa nitrogen and cell wall disappearance from ruminally-incubated dacron bags

Abstract: This reproduction was made from a copy of a manuscript sent to us for publication and microfilming. While the most advanced technology has been used to pho tograph and reproduce this manuscript, the quality of the reproduction is heavily dependent upon the quality of the material submitted. Pages in any manuscript may have indistinct print. In all cases the best available copy has been filmed.The following explanation of techniques is provided to help clarify notations which may appear on this reproduction. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 76 publications
2
16
0
Order By: Relevance
“…Formaldehyde treatment markedly reduced N degradation in the silage. Quantity and digestibility of bacterial amino acids entering the small intestine was similar between diets, however, the quantity of dietary amino acids reaching the small intestine was significantiy higher in sheep fed diets containing the treated silages.Similarly, a reduction in the rate of ruminal N degradation for alfalfa subjected to a sodium hyroxide treatment was reported by Farquhar (1985). …”
supporting
confidence: 65%
See 4 more Smart Citations
“…Formaldehyde treatment markedly reduced N degradation in the silage. Quantity and digestibility of bacterial amino acids entering the small intestine was similar between diets, however, the quantity of dietary amino acids reaching the small intestine was significantiy higher in sheep fed diets containing the treated silages.Similarly, a reduction in the rate of ruminal N degradation for alfalfa subjected to a sodium hyroxide treatment was reported by Farquhar (1985). …”
supporting
confidence: 65%
“…In addition to the technique used for fractionation of feed proteins, many other factors have been shown to impact ruminal protein degradation (Farquhar, 1985;Waghom et al, 1987;Weakley et al, 1989;Umunna et al, 1995 Farquhar (1985) reported that variation caused by animals was very little with steers fed hay, but differences in the rate of protein degradation were significant among steers fed a high grain diet. It is very likely that this difference was caused by differences in ruminal pH (5.75 vs. 6.35).…”
Section: Factors Affecting the N Degradation In Feedmentioning
confidence: 99%
See 3 more Smart Citations